2009
DOI: 10.1097/wnr.0b013e328331a51a
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-muscular coherence increases with tremor improvement after deep brain stimulation in Parkinson's disease

Abstract: Deep brain stimulation on the subthalamic nucleus has been used to relieve Parkinsonian motor symptoms. However, the underlying physiological mechanism has not been fully understood. Beta-band cortico-muscular coherence increases when healthy humans perform isometric contraction. We hypothesized that this might be a measure of symptomatic improvement in motor performance after subthalamic nucleus deep brain stimulation. Here, we measured the beta-band cortico-muscular coherence with magnetoencephalography from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Specifically, the introduction of temporal signal space separation (tSSS) (Taulu and Simola 2006) and null beamforming (Mohseni et al 2012) has been shown to successfully minimize the effects of the stimulator artifacts, facilitating studies examining the acute effects of DBS by comparing cortical activity during the DBS-on state to the DBS-off state. As a validity study, Park et al (2009) showed increased corticomuscular coherence in the beta band during STN stimulation. Another report supporting MEG feasibility during stimulation comes from the same group that developed the tSSS method for stimulator artifact removal (Airaksinen et al 2011).…”
Section: Network Effects Of Subthalamic Nucleus Stimulationmentioning
confidence: 99%
“…Specifically, the introduction of temporal signal space separation (tSSS) (Taulu and Simola 2006) and null beamforming (Mohseni et al 2012) has been shown to successfully minimize the effects of the stimulator artifacts, facilitating studies examining the acute effects of DBS by comparing cortical activity during the DBS-on state to the DBS-off state. As a validity study, Park et al (2009) showed increased corticomuscular coherence in the beta band during STN stimulation. Another report supporting MEG feasibility during stimulation comes from the same group that developed the tSSS method for stimulator artifact removal (Airaksinen et al 2011).…”
Section: Network Effects Of Subthalamic Nucleus Stimulationmentioning
confidence: 99%
“…The basic idea behind this approach is to separate sources within the brain from sources outside the brain using sensor geometry and Maxwell's equations. So far, tSSS was demonstrated to be suitable for DBS artefact removal during rest, auditory and somatosensory stimulation, as well as in a wrist extension task and changes in cortico-muscular coherence (Mäkelä et al, 2007;Park et al, 2009;Airaksinen et al, 2011Airaksinen et al, , 2012Airaksinen et al, , 2015. Therefore, tSSS has proven to be a powerful tool for MEG-DBS studies.…”
Section: Previous Approaches To Study Dbs Effectsmentioning
confidence: 97%
“…It has been observed that the medication and DBS may modify the tremor amplitude, regularity and frequency [4,41,42], movement speed [3,8,34,40,44,49,51,52], joint kinetics and muscle activation during movements [55], EMG burst patterns during movement [34,51,52] and the cortico-muscular coherence [25,37]. There is currently a lot of interest for characterizing EMG and kinematic signals of PD patients.…”
Section: Surface Electromyography and Kinematic Measurements In Pdmentioning
confidence: 99%